Hubungan Antara Iklim Organisasi Dengan Kepuasan Kerja Karyawan Di PT Gramedia Printing - , Nanung Prasetyo Ariadi, Sari Sitalaksmi, M.Mgt., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis explained about the relationship between organizational climate and job satisfaction at PT Gramedia Printing. The hypotheses are formed from theoretical construct that explain there is some relationship between organizational climate and job satisfaction. This research is quantitative research. The data was obtained through survey and some results of questionnaires, which are analyzed with statistical analysis method of Pearson Product Moment. The results of hypothesis using Pearson Product Moment correlation shows that the correlation value coefficient for organizational climate perceptions and job satisfaction is 0.778 with confidence level 95%. (Î±: 0.05) . Correlation coefficient 0.778 was show a positive relationship (positive correlation) which indicates those two variables of research have a direct relationship. Correlation coefficient value of 0.778 also shows that the levels of the relationship between those two variables are very significant. According on criteria of decisions, the conclusion of the result is: Ha was accepted. So for the result we can conclude that, there is a significant relationship between perceptions of organizational climate and job satisfaction of employees at PT Gramedia Printing.